Specific HR practices and employee commitment: the mediating role of job satisfaction. Issue 3 (16th January 2019) - Mahmood, Arshad; Akhtar, Muhammad Naseer; Talat, Usman; Shuai, Chuanmin; Hyatt, James C.
Abstract : Purpose: The purpose of this paper is to increase understanding of the influence mechanisms of specific HR practices variables – salary, job stability and job enrichment – upon employee commitment, through the mediating role of job satisfaction, in a developing country context. Crucially, these indicate employee commitment. Design/methodology/approach: The study analyzed three specific HR practices with a sample of 263 employees in the banking industry of Pakistan. A structural equation modeling methodology is adopted. Findings: The findings indicate that remuneration strategies were positively related to job satisfaction and employee commitment. Regarding the intervening impact of job satisfaction, this study found that it mediates only for non-monetary strategies between job satisfaction and employee commitment. Research limitations/implications: A key limitation is that this is a cross-sectional study, perhaps not generalizable over longitudinal approaches. Another limit is posed by the developing country context of this study, perhaps not applicable to some developed countries. Practical implications: From an HR perspective, managing salary structure is an ongoing issue. The proposed model suggests the use of specific practices about satisfaction and commitment as intermediate steps to manage employee commitment. Originality/value: The research offers a unique understanding from the developing country context of Pakistan. This provides a novel study conducted to examine employee commitment using the high-performance work practices model.